Producer of controversy : Stanley Kramer, Hollywood liberalism and the Cold War - Frost, Jennifer (CultureAmerica Series., 2017)
Through his career, politics, and films, Hollywood filmmaker Stanley Kramer significantly shaped American culture during the Cold War.